Práticas de gestão estratégica de custos e Posicionamento estratégico: um estudo no setor do agronegócio brasileiro - Grando, Vidamar (Universidade do Vale do Rio dos Sinos, 2017)
This study aimed to identify the strategic management practices of the most used costs according to the competitive strategies adopted by companies of Brazilian agribusiness sector. For that, a survey was realized between the 400 biggest companies in agribusiness sector, which resulted in 169 valid answers. The analysis of answers frequency indicated a high level of the utilization in 6 the 14 investigated practices, hith emphasis on logistic costs, standart cost and quality cost. The strategy if competitive positioning of leadership in costs is the most used, being adopted in 43 companies, while the competitive strategy for differentiation is used in 27 companies and by focus by 9 companies. There are a large number of companies (90) identified with indefinite strategic positioning or with no strategy (mid-term). The analysis was applied to the criation os factors that could relate the practices of GEC with the competitive strategies, but, the majority of results has being comb ined in one unique factor. Among the 79 companies classified with strategic positioning of low cost, differentiation or focus, it was possible to conclude both strategies use the GEC practices logistics costs, cost of quality and standard cost. The GEC practices costing attributes, environmental costs, target cost and TCO are most commonly used in companies that position themselves with low cost strategies. The practices environmental costs, TCO, life cycle cost and interorganizational costs are more commonly used in companies whose strategy is by differentiating. In companies that seek competitive advantage through the use of a strategy of focus through product differentiation use 12 of the 14 cost practices analyzed are used.
Keywords: Estratégias competitivas; Gestão estratégica de custos; Posicionamento estratégico; Competitive strategies; Strategic cost management; Strategic positioning; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis